The "Edge Effect" in Measuring the Thickness of Powder Paint. (2015) - Jozsef, Boer; Blaga, Petruţa
Abstract: In the process of checking the quality of the layer of paint applied on the product, one of the quality control operations is measuring the thickness of the layer of paint, an operation which is an important factor in assuring the conformity of the product's quality. The measurement is done with the help of a device that explores the principle of interaction between the metallic surface and a low frequency electromagnetic field.